FAKTOR-FAKTOR DALAM PEKERJAAN IBU YANG MENGHAMBAT PEMBERIAN ASI EKSKLUSIF (STUDI LITERATUR) - Fitriyani Wijayanti; Ani Margawati; Mohammad Zen Rahfiludin (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Exclusive breastfeeding is the action of mothers who only give milk to babies aged 0 to 6 months, without the addition of other foods and drinks. The success of exclusive breastfeeding can be influenced by inside and outside factors. One of the factors that can influence exclusive breastfeeding is working mothers. The purpose of this study is to determine the factors in the mother's work that can hinder exclusive breastfeeding. The method used in this study is Literature review. Data collection is obtained through Google Scholar, Science Direct, and Springer. The keywords used in the article search are